2001
DOI: 10.1103/physrevb.64.075114
|View full text |Cite
|
Sign up to set email alerts
|

Extended tail states in an imaginary random potential

Abstract: Non-Hermitean operators may appear during the calculation of a partition function in various models of statistical mechanics. The tail eigen-states, having anomalously small real part of energy Re(ε), became naturally important in this case. We consider the distribution of such states and the form of eigenfunctions for the particle propagating in an imaginary random potential (the model motivated by the statistics of polymer chains). Unlike it is in the Hermitean quantum mechanics, our tail states are sufficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
(27 reference statements)
1
26
0
Order By: Relevance
“…Other studies have focused on randomscattering models on the Cayley tree [18,19,20]. More recently, the interest in Anderson localization on the Cayley tree has been revived by the question of many-body localization [21], because the geometry of the Fock space of many-body states was argued to be similar to a Cayley tree [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on randomscattering models on the Cayley tree [18,19,20]. More recently, the interest in Anderson localization on the Cayley tree has been revived by the question of many-body localization [21], because the geometry of the Fock space of many-body states was argued to be similar to a Cayley tree [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A natural hierarchy of couplings occurs in many physical systems, For example, a spin of a nucleus may be coupled to the electromagnetic modes of a cavity in which it is situated, and these in turn may be coupled to the modes of a larger box or the vacuum [2]. Hierarchical systems were studied [3,4,5,6,7,8,9,10] but the time dependence for the model we present was not investigated. FIG.…”
mentioning
confidence: 99%
“…We also observe a non-monotonic behavior of P (E) near the band edges, which can be understood in terms of Lifshitz tail states [66]. This kind of localized states originate from rare fluctuations of the on-site potential, where the values of the potential inside some sufficiently large volume turn out to be close to each other [30].…”
Section: Long-range Correlationsmentioning
confidence: 80%
“…Another interesting direction in the study of localization is to consider the effects of non-Hermitian random potentials, which include imaginary scalar and vector potentials and PT -symmetric complex potentials [28][29][30][31][32][33][34][35][36][37][38]. It has been reported that these systems show many interesting localization properties such as a transition from a real to a complex spectrum [28].…”
Section: Introductionmentioning
confidence: 99%